Association between human leukocyte antigen E expression and outcomes in solid tumors: a systematic review and meta-analysis - Benitez Fuentes, Javier David; Bartolome Arcilla, Jorge; Lazaro Sanchez, Antonio David; de Luna Aguilar, Alicia; Mohamed Mohamed, Kauzar; Guevara-Hoyer, Kissy; Ballestin Martinez, Pablo; Borregon Rivilla, Miguel; Ferrandez Arias, Asia; Sánchez-Ramon, Silvia; Ocaña, Alberto (Frontiers in Oncology, 2025)
BackgroundImmunotherapy has gained momentum with the discovery of novel antibodies targeting immunosuppressive proteins. HLA-E, a non-classical major histocompatibility complex class I (MHC-I) protein, exhibits immunosuppressive properties, potentially influencing tumor immune evasion mechanisms. The association between Human Leukocyte Antigen E (HLA-E) expression and outcomes in solid tumors remains unclear.MethodsA systematic review of MEDLINE, Scopus, and the Cochrane Library up to March 15, 2024, was conducted following the PRISMA guidelines. Studies investigating HLA-E expression in solid tumors and its association with OS and DFS were included. Statistical analysis was performed using Comprehensive Meta-Analysis (version 3.0) with random-effects models.ResultsAfter screening 657 articles, 11 studies were included, comprising a total of 1781 patients. The studies encompassed a variety of cancer types, follow-up periods, and staging details, with the majority focusing on non-metastatic cases. Notably, three studies evaluated colorectal cancer, while others focused on pancreatic, esophageal, brain, renal cell, gastric, endometrial, cervical, and hepatocellular carcinomas. The mean age of the patients was 59.81 ± 2.01 years, and the median follow-up period was 57.45 ± 8.91 months. HLA-E expression demonstrated no statistically significant association with OS (HR 0.913, 95% CI = 0.567-1.469; P=0.707), with significant heterogeneity observed (I2 = 84%). However, HLA-E non-expression was significantly associated with improved DFS (HR 1.406, 95% CI = 1.027-1.930; P=0.03), with moderate heterogeneity (I2 = 45%).ConclusionThis systematic review highlights that HLA-E expression in solid tumors could be a biomarker of better prognosis, measured by DFS. These findings align with the clinical benefit observed for agents targeting this pathway. However, further studies should be performed to confirm these preliminary observations.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024527598, identifier CRD42024527598.